Ancient poetry in contemporary Chinese tourism. (June 2016) - Yu, Xiaojuan; Xu, Honggang
Abstract: Classical poetry is an important part of Chinese culture. This study explores its roles in contemporary Chinese tourism based on participant observation of tourist destinations in the Three Gorges and surrounding area along the Yangtze River and content analysis of tourism guidebooks. Classical poetry is used to guide Chinese tourists in terms of what to gaze at and how to gaze. Specifically, first, poets and their poems create historical and cultural value for a place, which forms an essential foundation for its attractiveness as an object for Chinese tourists gaze. Second, poems may be used to enhance tourists' aesthetic appreciation of a landscape along the spatial and temporal dimensions, creating transcending poetic experiences. Such influence of classical poetry exemplifies the cultural continuity in China that should be well understood and considered in contemporary tourism. Implications in tourism development and marketing, aesthetic experience creation, environmental interpretation, and literary tourism are discussed. Highlights: Ancient poetry continues to influence Chinese tourism in terms of what and how to gaze. Ancient Chinese poets and their poems create value for places as tourism attractions. Poems may help enhance tourists' landscape appreciation and aesthetic experience. Poetry may be combined with scientific knowledge to improve environmental interpretation.